Research progress on the analysis of resistance genes and mechanisms of wheat fusarium crown rot - Zhou, Heng; Cao, Wenxin; Li, Yao; Zhang, Qiqi; Liu, Fangfang; Wan, Yingxiu (Frontiers in Plant Science, 2025)
Fusarium crown rot (FCR) of wheat represents a critical challenge to global wheat production. Discovering disease-resistant genes and analyzing their resistance mechanisms are crucial for breeding resistant varieties and controlling the disease. In recent years, molecular biology and genomics technologies have advanced rapidly. This has enabled remarkable progress in discovering FCR-resistant genes in wheat. Through genetic mapping, association analysis, and mutant screening, multiple gene loci related to wheat FCR resistance have been identified. For instance, the gene locus Qfcr.sicau-4B on chromosome 4B was found to significantly enhance FCR resistance by regulating cell wall lignification, while the Fhb1 locus on chromosome 3B, though originally identified for fusarium head blight resistance, has shown cross-resistance to crown rot in some genetic backgrounds. In terms of mechanism analysis, studies show that these resistant genes combat pathogen invasion through multiple pathways. For example, they can activate the plant immune system, regulate defense-related gene expression, enhance cell wall structural stability, and mediate reactive oxygen species (ROS) metabolism. The ROS detoxification pathway, exemplified by the TaCAT1 gene encoding catalase, efficiently scavenges hydrogen peroxide to prevent oxidative damage during pathogen infection. Additionally, the mitogen-activated protein kinase (MAPK) cascade pathway, such as the TaMPK3-TaMPK6 module, has been shown to phosphorylate and activate transcription factors that induce defense gene expression. Additionally, signal transduction pathways play a bridging role in resistant gene function. Pathways such as the MAPK cascade and plant hormone signal transduction are involved in transmitting and amplifying resistance signals. This review systematically reviews methods for discovering wheat FCR-resistant genes, identified resistant genes and their functions, and deeply analyzes resistance mechanisms. Its aim is to provide a theoretical basis and technical support for genetic improvement and sustainable control of wheat FCR.